2019
DOI: 10.3201/eid2501.180807
|View full text |Cite
|
Sign up to set email alerts
|

Variable Protease-Sensitive Prionopathy Transmission to Bank Voles

Abstract: Variably protease-sensitive prionopathy (VPSPr), a recently described human sporadic prion disease, features a protease-resistant, disease-related prion protein (resPrPD) displaying 5 fragments reminiscent of Gerstmann-Sträussler-Scheinker disease. Experimental VPSPr transmission to human PrP–expressing transgenic mice, although replication of the VPSPr resPrPD profile succeeded, has been incomplete because of second passage failure. We bioassayed VPSPr in bank voles, which are susceptible to human prion strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 40 publications
3
25
0
Order By: Relevance
“…It has been shown that the infectivity of VPSPr is lower, if present, compared to that of sCJD [ 29 , 30 , 31 ]. To compare aggregation seeding activity of PrP Sc of VPSPr with that of PrP Sc from other more common sporadic and familial prion diseases, we conducted a RT-QuIC assay of serial dilutions of brain homogenate seeds with three genotypes of VPSPr, sCJDMV2 and GSS linked to PrP P102L mutation.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the infectivity of VPSPr is lower, if present, compared to that of sCJD [ 29 , 30 , 31 ]. To compare aggregation seeding activity of PrP Sc of VPSPr with that of PrP Sc from other more common sporadic and familial prion diseases, we conducted a RT-QuIC assay of serial dilutions of brain homogenate seeds with three genotypes of VPSPr, sCJDMV2 and GSS linked to PrP P102L mutation.…”
Section: Resultsmentioning
confidence: 99%
“…The use of bank voles as a model system has certainly been pivotal for the present study. Indeed, bank voles and transgenic mice expressing bank vole PrP have been shown to faithfully propagate prion strains from various species ( 26 , 31 , 32 ), including prion strains that are difficult to transmit in other animal models ( 33 , 34 ). We based our conclusions on a careful comparison of incubation times and pathological phenotypes induced by natural CWD isolates along three serial passages in the new host.…”
Section: Discussionmentioning
confidence: 99%
“…These results showed striking similarities to those obtained in a subgroup of GSS cases. More recently, VPSPr inocula efficiently transmitted the disease to bank voles (Bv109M, Bv109I) [180]. Despite the low attack rate after the first passage (5% for Bv109M, 35% Bv109I), all inoculated animals developed the disease and showed dramatically reduced survival times (about 50%) after the secondary transmission, suggesting a consistent species barrier between humans and bank voles.…”
Section: Characterization Of Human Prion Strains By Experimental Tmentioning
confidence: 99%
“…Despite the low attack rate after the first passage (5% for Bv109M, 35% Bv109I), all inoculated animals developed the disease and showed dramatically reduced survival times (about 50%) after the secondary transmission, suggesting a consistent species barrier between humans and bank voles. Intriguingly, the affected animals showed three histo-molecular phenotypes, apparently unrelated to genotype at codon 129, with transmission characteristics reproducing those of PrP Sc type 1 (21 kDa) and 2 (19 kDa) sCJD, and GSS expressing the ~7 kDa PrP Sc fragment [180].…”
Section: Characterization Of Human Prion Strains By Experimental Tmentioning
confidence: 99%